GENERALIZATION OF THE RULE COUNTING OF THE FREE VARIABLES IN DOUBLE-EVEN PANDIAGONAL MAGIC SQUARES - Lafta, Ala'a (Iraqi Journal of Science, 2024)
In this paper, we generalize the rule of counting the number of the free variables in the double – even pandiagonal magic squares; our method is not based on the direct computation of the solution of the linear system. Instead, We deduce this rule by applying the theorems and methods of linear algebra , finally put algorithm of the solution .